Dynamics Simulation Analysis of Single Row Four Point Contact Ball Slewing Bearing - Jian Zhao; Tingqiang Yao; Ruibo Chen (Jixie chuandong)
Based on multi-body dynamics method and Hertz contact theory， the Impact function is applied to define four-point contact of steel ball in slewing bearing and meshing contact action of straight teeth with internal teeth. And the multi-body contact dynamics model of four-point contact ball slewing bearing is established by the utilization of Adams simulation platform. The simulated and theoretical values of the angular velocity， transmission ratio and static load of the slewing bearing are compared and testified， and the influence on the rotational speed and load on the dynamic characteristics of the slewing bearing is analyzed. It follows that under the action of axial load alone， the higher the gear drive speed is， the larger the meshing force is， and the vibration get smaller， however， the four-point contact force between the steel ball and the raceway does not change much. When the rotation speed is constant， the axial load and the overturning moment act separately， the overturning moment has a greater impact on the stability of the slewing bearing.